2021
DOI: 10.3390/toxics9100234
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Calculation on the Reaction Mechanisms, Kinetics and Toxicity of Acetaminophen Degradation Initiated by Hydroxyl and Sulfate Radicals in the Aqueous Phase

Abstract: The •OH and SO4•− play a vital role on degrading pharmaceutical contaminants in water. In this paper, theoretical calculations have been used to discuss the degradation mechanisms, kinetics and ecotoxicity of acetaminophen (AAP) initiated by •OH and SO4•−. Two significant reaction mechanisms of radical adduct formation (RAF) and formal hydrogen atom transfer (FHAT) were investigated deeply. The results showed that the RAF takes precedence over FHAT in both •OH and SO4•− with AAP reactions. The whole and branch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…In the KiSThelP, the tunneling correction factor was determined by the Wigner correction, χ(T) [ 43,46,47 ] that was calculated based on the imaginary frequency lm( v ‡ ) of the transition states (TSs) as the following equation: [ 43 ] χ()Tgoodbreak=1goodbreak+124h0.25emlm()vkbT2…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the KiSThelP, the tunneling correction factor was determined by the Wigner correction, χ(T) [ 43,46,47 ] that was calculated based on the imaginary frequency lm( v ‡ ) of the transition states (TSs) as the following equation: [ 43 ] χ()Tgoodbreak=1goodbreak+124h0.25emlm()vkbT2…”
Section: Methodsmentioning
confidence: 99%
“…The ∆G ‡ values of HT reactions were determined by the Gibbs energy differences between reactants and the transition state (TS), whereas Marcus's theory was applied to calculate ∆G ‡ of the SET reaction. [44,45] In the KiSThelP, the tunneling correction factor was determined by the Wigner correction, χ(T) [43,46,47] that was calculated based on the imaginary frequency lm(v ‡ ) of the transition states (TSs) as the following equation: [43] 𝜒(𝑇…”
Section: Introductionmentioning
confidence: 99%
“…In the KiSThelP, the Wigner correction, χ(T ), is applied to acquire the tunnelling correction factor for all the elementary reactions [33,36,37]. This factor was determined based on the imaginary frequency lm(v ‡ ) of the TSs as follows [33]:…”
Section: Methodsmentioning
confidence: 99%
“…In the KiSThelP, the Wigner correction, χ ( T ), is applied to acquire the tunnelling correction factor for all the elementary reactions [33,36,37]. This factor was determined based on the imaginary frequency lm( v ‡ ) of the TSs as follows [33]:χfalse(Tfalse)=1+true0124(h normallm(v)kbT).The rate of reaction was therefore calculated as the following equation:kfalse(Tfalse)=χfalse(Tfalse)×kTSTfalse(Tfalse).…”
Section: Methodsmentioning
confidence: 99%
“…They revealed that ACT had a significant impact on the number of Lemna minor fronds (EC 50 = 446.6 mg L −1 ), but there was no effect on Lemna gibba . Xu et al 106 studied the acute and chronicle effects of ACT onto three different aquatic species (i) fish, (ii) green algae and (iii) daphnia. The acute toxicity values were LC 50 = 63.1 mg L −1 for daphnia and LC 50 = 323 mg L −1 for fish, and EC 50 = 26.3 mg L −1 .…”
Section: The Toxicity Assessment Of Act and Its By-productsmentioning
confidence: 99%